Diversity, Rankings and Their Determinants – General Issues and Poland’s Experience (Economic and Political Thought, 2012)
The article aims to answer several key questions, namely: What doesdiversity in higher education concern? What is the relationship betweendiversity and university rankings – do and what dimensions of higher educationdiversity create favorite conditions for reaching high positions in rankings?What is the role of competition on the one hand and government policy onthe other hand in maintaining or upgrading a position in rankings? Whatother conditions of the functioning of universities are crucial for diversityand the improvement of productivity and scientific quality? And last butnot least, in what conditions do the Polish universities function and whatshould be done to upgrade their positions in the global rankings and maintaintheir diversity? The answers to these questions are surprising and have greatutilitarian importance.